Probiotic Lactobacillus rhamnosus GG prevents alveolar bone loss in a mouse model of experimental periodontitis. (11th December 2017) - Gatej, Simona M.; Marino, Victor; Bright, Richard; Fitzsimmons, Tracy R.; Gully, Neville; Zilm, Peter; Gibson, Rachel J.; Edwards, Suzanne; Bartold, Peter M.
Abstract: Aim: This study investigated the role of Lactobacillus rhamnosus GG (LGG) on bone loss and local and systemic inflammation in an in vivo mouse model of experimental periodontitis (PD). Materials and Methods: Experimental PD was induced in mice by oral inoculation with Porphyromonas gingivalis and Fusobacterium nucleatum over a period of 44 days. The probiotic LGG was administered via oral inoculation or oral gavage prior to, and during disease induction. The antimicrobial activity of LGG on the inoculum was also tested. Alveolar bone levels and gingival tissue changes were assessed using in vivo microcomputed tomography and histological analysis. Serum levels of mouse homologues for IL‐8 were measured using multiplex assays. Results: Pre‐treatment with probiotics either via oral gavage or via oral inoculation significantly reduced bone loss ( p < .0001) and gingival inflammation ( p < .0001) when compared with PD group. Oral gavage treatment group had significantly less tartrate‐resistant acid phosphatase positive cells ( p < .02) then PD group. LGG showed no antimicrobial activity against P. gingivalis and F. nucleatum . Conclusions: Lactobacillus rhamnosus GG effectively suppresses bone loss in a mouse model of induced PD irrespective of the mode of administration.